Microfinance, Poverty and Youth Unemployment of Nigeria: A Review (Global Journal of Human-Social Science, 2012)
This paper acknowledges that poverty is a curse, not only for the individual who is poor, but for remainder of the community, nation and global society at large. Poverty is the violation of the basic norm of our civilization. Yet poverty persists and it is evident globally. In reality, unemployment is thought to be the basic cause of Poverty. The severity of poverty isclearly evident in underdeveloped countries; while it is often disguised in most developed nations. The measure of poverty is misleading too; as it hardly reflects true nature. Poverty may arise either from simple or very complex reasons. In Nigeria the poverty and chronic youth unemployment are both apparent. This paper examines if Nigerian microfinance programs are being effective in curbing the extent of unemployment and sever poverty from Nigeria.Accordingly, this paper investigates thegrameen bank's microfinancemodel developed by the Nobel Laureate Dr. Yunusof Bangladesh for comparison.
Keywords: Microfinance; Unemployment; Acknowledges; Isclearly; Civilization